2021
DOI: 10.1016/j.sopen.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of perforated appendicitis: Impact of the C-reactive protein level

Abstract: Background Perforated appendicitis without an associated abscess necessitates emergency surgery. However, it is difficult to predict the presence of perforation before surgery, and the predictive factors are still unclarified. Our purposes were to characterize a patient population with perforated appendicitis without an associated abscess to identify the preoperative predictive factors of appendiceal perforation. Methods We retrospectively identified 150 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies have reported a higher incidence of appendiceal perforation among vulnerable populations, including the elderly, racial minorities, individuals with high comorbidity, low socioeconomic status, and those without insurance [20][21][22] . In a recent study involving 150 patients with acute appendicitis, older individuals had a higher rate of appendiceal perforation compared to younger patients (64.5 years vs 38.5 years, p < 0.001) 23 . However, Our study found that age and the Charlson Comorbidity Index (aCCI) were not the main risk factors for appendiceal perforation, as no statistically signi cant differences were observed in the multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported a higher incidence of appendiceal perforation among vulnerable populations, including the elderly, racial minorities, individuals with high comorbidity, low socioeconomic status, and those without insurance [20][21][22] . In a recent study involving 150 patients with acute appendicitis, older individuals had a higher rate of appendiceal perforation compared to younger patients (64.5 years vs 38.5 years, p < 0.001) 23 . However, Our study found that age and the Charlson Comorbidity Index (aCCI) were not the main risk factors for appendiceal perforation, as no statistically signi cant differences were observed in the multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 92%
“…The CRP level is used to support clinical data in making an operation decision (26)(27)(28) . It is stated that CRP elevation is an important marker in differentiating complicated appendicitis (5,8) . The CRP value increases more in children with high inflammatory response, such as complicated appendicitis (24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Although many inflammatory markers are used for the diagnosis of acute complicated appendicitis, there is still no specific biomarker. It has been reported that high C-reactive protein (CRP) is an important marker in differentiating acute complicated appendicitis (5,8) . Total serum bilirubin (TSB), which has recently been accepted as a marker in diagnosing complicated appendicitis, also increases in infectious diseases involving organs other than the liver (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Bilirubin levels are highly specific for the diagnosis of complicated appendicitis; a 2.0-fold increase in the likelihood of complicated appendicitis was observed in patients with elevated bilirubin levels ( Noh et al, 2012 ). In addition, total bilirubin > 21.38 mol/L was a predictor of appendicitis perforation ( Yamazaki et al, 2021 ). As serum bilirubin level is an economical, simple, and available laboratory index, it should be recommended for preliminary evaluation of acute appendicitis in pediatric patients.…”
Section: Single Indexmentioning
confidence: 99%